Transformative Learning Theory in Higher Education: Perspective Transformation for Students of a Department of Education in Greece - Liodaki, Niki; Karalis, Thanassis (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The following article explores the perspective transformation in Greek higher education using the Learning Activities Survey (LAS) questionnaire and semi-structured interviews. More specifically, the research occurred in the Department of Educational Sciences and Early Childhood Education at the University of Patras, Greece. The results have shown that 93.3% of the students have gone through two to five phases with the disorienting dilemma phase concentrating the highest percentage (58.7%). The students experienced changes regarding their way of thinking and behavior, changes in the perceptions as regards their profession and in some cases changes in their beliefs or expectations.